Factors Influencing Fish Purchase and Consumption Behaviour of Koraga and Soliga Tribes, Karnataka, India (Indian Journal of Extension Education, 2023)
The study carried out in 2021-2022 investigates fresh and dried fish consumption patterns and factors influencing fish purchase among Koragas and Soligas; two major tribes of Karnataka, India. 400 fish-consuming tribal households were surveyed and per capita fish consumption was estimated at 1.04 and 2.02 kg/person/month for Koragas and Soligas respectively. Mackerel and Sardine were the two most important species preferred by the Koragas while Tilapia and Catla were the preference among Soligas. Among the 15 factors studied; the ones that were ranked with the highest contribution towards the fish purchase of Koragas were the ‘price of fish’ (7.68) and the ‘availability of favourite fish’ (7.36). Soligas ranked the ‘availability of favourite fish’ (10.42) as the most contributing factor followed by ‘convenience perception’ (6.69). Increasing awareness about the health benefits of fish consumption and building the capacity of tribes to prepare culturally compatible fish-based products can aid in improving fish consumption. The results of the study will be of utility to health department officials and policymakers in planning strategies to increase fish consumption and alleviate malnutrition among these tribes.